Looks like Tuberculous Meningitis, But Not: A Case of Rhinocerebral Mucormycosis with Garcin Syndrome - Yang, HongNa; Wang, CuiLan (Frontiers in Neurology, 2016)
Rhinocerebral mucomycosis (RCM) as an emerging opportunistic, angioinvasive and devastating fungi infection with high mortality is difficult to be diagnosed early because of the lack of specific clinical features or manifestations. Garcin syndrome is more often caused by skull base and rhinopharyngeal tumors or metastases, and basal meningitis. We reported that an aged diabetic man, involved nearly all cranial nerves (Garcin syndrome), who was at first suspected to be suffered from tuberculous meningitis (TBM), ultimately developed typically progressing RCM. Diagnosis was made to find the presence of mucormycosis in the infected tissue by biopsy.